2013
DOI: 10.1088/1748-6041/8/5/055009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced chemoresistance of squamous carcinoma cells grown in 3D cryogenic electrospun scaffolds

Abstract: It is critically important to study head and neck squamous cell carcinoma tumorigenic mechanisms in order to gain a better understanding of tumor development, progression, and treatment. Unfortunately, a representative three-dimensional (3D) model for these evaluations has yet to be developed. The purpose of this study was to replicate tumor extracellular matrix (ECM) morphology utilizing electrospinning technology. First, the tumor ECM was evaluated by decellularizing tumor samples and analyzing the fibrous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The diameter of the fibre determines the pore size of the scaffold, and this determines how well cells will penetrate into a scaffold (Balguid et al 2009;Baker et al 2008;Ju et al 2010). Techniques such as cryogenic electrospinning have shown to create structures with a much greater porosity, enabling cell infiltration throughout the scaffold (Leong et al 2013;Bulysheva et al 2013;Leong et al 2009); this can be controlled by modifying the humidity of the spinning environment, changing the amount of ice crystal formation on the cooled mandrel (Leong et al 2013). It is essential in the culture of a complex 3D system for a distribution of cells throughout the scaffold, increasing the porosity within electrospun scaffolds by cryogenic electrospinning allows for this greater cell distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diameter of the fibre determines the pore size of the scaffold, and this determines how well cells will penetrate into a scaffold (Balguid et al 2009;Baker et al 2008;Ju et al 2010). Techniques such as cryogenic electrospinning have shown to create structures with a much greater porosity, enabling cell infiltration throughout the scaffold (Leong et al 2013;Bulysheva et al 2013;Leong et al 2009); this can be controlled by modifying the humidity of the spinning environment, changing the amount of ice crystal formation on the cooled mandrel (Leong et al 2013). It is essential in the culture of a complex 3D system for a distribution of cells throughout the scaffold, increasing the porosity within electrospun scaffolds by cryogenic electrospinning allows for this greater cell distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Fibre diameter has shown to affect the gene expression of cells (Hodgkinson et al 2014;Wang et al 2014;Bean & Tuan 2015), and cryogenic scaffolds have shown to effect the behaviour of scaffolds and give a better representation on an in vivo environment for drug development (Bulysheva et al 2013). We found that small diameter fibres at 7 days had a significant reduction in KIM-1 expression compared to tissue culture plastic in both aligned and cryogenic scaffolds, possibly indicating healthier cells (Waanders et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A, cell proliferation was similar for both 2D and sandwich microenvironments after 6 h of culture, but significantly lower within sandwich conditions after 24 h, as reported to occur in vivo. 32 Smaller but significant differences can be also observed after 24 hours depending on whether the sandwich was assembled immediately (SW t0 ) or after 3 h of culture (SW).…”
Section: Cell Proliferation In Fn-matrix Sandwich Microenvironmentsmentioning
confidence: 99%
“…Collagen-based electrospun scaffolds were used with C4-2B cells (prostate cancer) to recapitulate tumour progression and were Page 16 of 44 A c c e p t e d M a n u s c r i p t shown to be resistant to docetaxel and camptothecin [167]. Electrospun silk fibres loaded with HN12 cells (metastatic squamous cell carcinoma) presented comparable cell proliferation, differentiation, infiltration and chemoresistance to that of in vivo HN12 mouse xenografts [168].…”
Section: Fibresmentioning
confidence: 99%